Real-world Time to Positivity of 2 Widely Used Commercial Blood Culture Systems in Patients With Severe Manifestations of Sepsis: An Analysis of the FABLED Study. (23rd August 2020) - Butler-Laporte, Guillaume; Yansouni, Cedric P; Paquette, Katryn; Lawandi, Alexander; Stabler, Sarah N; Akhter, Murtaza; Davidson, Adam C; Gavric, Marko; Jinah, Rehman; Saeed, Zahid; Demir, Koray; Sangsari, Sassan; et al.
Abstract: Background: Of all microbiological tests performed, blood cultures have the most impact on patient care. Timely results are essential, especially in the management of sepsis. While there are multiple available blood culture systems on the market, they have never been compared in a prospective study in a critically ill population. Methods: We performed an analysis of the FABLED study cohort to compare culture results and time to positivity (TTP) of 2 widely used blood culture systems: BacT/Alert and BACTEC. In this multisite prospective study, patients with severe manifestations of sepsis had cultures drawn before antibiotics using systematic enrollment criteria and blood drawing methodology allowing for minimization of pre-analytical biases. Results: We enrolled 315 patients; 144 had blood cultures (47 positive) with BacT/Alert and 171 with BACTEC (53 positive). Patients whose blood cultures were processed using the BacT/Alert system were younger (median, 64 vs 70 years; P = .003), had a higher proportion of HIV (9.03% vs 1.75%; P = .008) and a lower qSOFA ( P = .003). There were no statistically significant differences in the most commonly identified bacterial species. TTP was shorter for BACTEC (median [interquartile range IQR], 12.5 [10–14] hours) compared with BacT/Alert (median [IQR], 17 [14–21] hours; P < .0001). Conclusions: In this large prospective multi-centre study comparing the two blood culture systems among patients with severe manifestations of sepsis, and using a rigorous pre-analytical methodology, the BACTEC system yielded positive culture results 4.5 hours earlier than BacT/Alert. These results apply to commonly isolated bacteria. However, our study design did not allow direct comparison of TTP for unusual pathogens nor of clinical sensitivity between systems. More research is needed to determine the clinical implications of this finding.